TINJAUAN Penggunaan Suspensi Sel dalam Kultur In Vitro - Sri Hutami (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2009)
Cell suspension culture could be defined as aprocess that allows rapidly dividing homogenous suspensionof cells to grow in liquid nutrient media. There are two maintypes of suspension cultures: (1) Batch cultures in whichcells are nurtured in a fixed volume of medium until growthceases and (2) Continuous cultures in which cell growth ismaintained by continuous replenishment of sterile nutrientmedia. Plant cell suspension cultures are mostly used for thebiochemical investigation of cell physiology, growth, metabolism,protoplast fusion, transformation and for large scaleproduction of seed by bioreactor and production of secondarymetabolites. Contamination is one of the largest problemswhen dealing with cell cultures. Differences betweenthe products of cell suspension culture and whole plant arefrequently observed. These phenomena’s may be resultedfrom lack of differentiation and organization and cell cultureinducedvariation. Utilization of cell suspension culture inIndonesia is still limited, some of them for mass productionof plantation seed with bioreactor system and for productionof secondary metabolites. The success of this study give theopportunity for mass production of seeds from other plantsand also production of secondary metabolites.